Pharmacological Modulation of Lung Carcinogenesis in Smokers: Preclinical and Clinical Evidence. (February 2016) - De Flora, Silvio; Ganchev, Gancho; Iltcheva, Marietta; La Maestra, Sebastiano; Micale, Rosanna T.; Steele, Vernon E.; Balansky, Roumen
Abstract : Many drugs in common use possess pleiotropic properties that make them capable of interfering with carcinogenesis mechanisms. We discuss here the ability of pharmacological agents to mitigate the pulmonary carcinogenicity of mainstream cigarette smoke. The evaluated agents include anti-inflammatory drugs (budesonide, celecoxib, aspirin, naproxen, licofelone), antidiabetic drugs (metformin, pioglitazone), antineoplastic agents (lapatinib, bexarotene, vorinostat), and other drugs and supplements (phenethyl isothiocyanate, myo-inositol, N -acetylcysteine, ascorbic acid, berry extracts). These drugs have been evaluated in mouse models mimicking interventions either in current smokers or in ex-smokers, or in prenatal chemoprevention. They display a broad spectrum of activities by attenuating either smoke-induced preneoplastic lesions or benign tumors and/or malignant tumors. Together with epidemiological data, these findings provide useful information to predict the potential effects of pharmacological agents in smokers. Trends: Many drugs possess pleiotropic properties that, potentially, would be expected to interfere with carcinogenesis mechanisms. Assessment of protective effects in humans is exceedingly challenging, and there are difficulties in reproducing smoke carcinogenicity in experimental animals. A murine model can be used to evaluate pharmacological agents by simulating interventions either in current smokers or in ex-smokers, or even mimicking transplacental chemoprevention. Reviewed agents include anti-inflammatory drugs, antidiabetic drugs, antineoplastic agents, and other drugs and supplements. These drugs display a broad spectrum of activities by attenuating smoke-induced preneoplastic lesions or benign tumors (adenomas), and/or malignant tumors in mouse lungs. Both experimental and epidemiological data contribute to predict the possible effects of pharmacological agents in smokers.